A Comparison of Prenatal Exposures in Children with and Without A Diagnosis of Autism Spectrum Disorder in an Atlantic Canadian City. (1st June 2016) - Saunders, A
Abstract: BACKGROUND: Autism spectrum disorder (ASD) is a multifactorial disorder characterized by varying deficits in social interactions, disordered communication and repetitive behaviour patterns. Signs that a child has autism are present in the early developmental stages and the symptoms cause significant impairment in many areas of functioning, including social, educational/occupational, and performance of everyday activities. There have been established genetic correlates and noticeable heredity with ASD diagnoses, but so far chromosomal genetic changes have only been found in approximately 25% of children with autism who were studied and there was no single variance that predominated. This signifies that there may be other external factors at play for autism to develop from preexisting genetic risk. Current studies suggest that prenatal exposures are more important to future autism diagnoses than those that happen after birth; there appears to be disruption of neuron gene networks in the cell cycle, protein folding, DNA damage repair and cell apoptosis. Potential prenatal triggers are the focus of this study, with interest to one geographical area in Atlantic Canada. OBJECTIVES: The study focused on the presence of environmental exposures during pregnancy in children who developed autism spectrum disorder and those who did not, with a specific focus on a specific Atlantic Canadian city. Exposures inquired about included: acetaminophen/ paracetamol use, air pollution, fever, parental age, maternal diabetes, prenatal vitamin use, workplace exposures, recreational drug use, seafood consumption, obesity, and maternal thyroid issues. DESIGN/METHODS: Mothers of children aged 0-10 years were asked to participate in a telephone interview regarding environmental exposures during their pregnancy. This was followed up by a prenatal chart review. There were two groups of participants: 107 from the autism group and 108 from the non-autism group. The data was analyzed with univariate tests and a logistic regression. RESULTS: Univariate analysis revealed significant differences between groups for presence of siblings with ASD, presence of family members with ASD, presence of fever, use of medications, use of cigarettes, and gesta-tional age at the start of prenatal vitamins. Logistic regression analysis found significance with use of medications, use of cigarettes, and gesta-tional age at the start of prenatal vitamins. CONCLUSION: The use of medications and cigarettes during pregnancy are associated with an increased rate of autism diagnosis. As well, a later starting date for use of prenatal vitamins was associated wth autism. Working towards an understanding of factors that come together to create a diagnosis of autism will be helpful for families, physicians, and allocating government resources.